Studies on the design of a composition of gel for the treatment of inflammatory diseases of the joints - Vyshnevska, Liliia; Strilets, Oksana; Vladyslav, Postoy (ScienceRise: Pharmaceutical Science, 2018)
The aim: the aim of our work was to experimentally substantiate the effectiveness of antimicrobial preservatives in the design of the composition of the combined gel for the treatment of acute and chronic inflammation of the joints. Methods: biological pharmacopoeial method of research was used (research of the effectiveness of antimicrobial preservatives). Results. All drugs must meet the requirements of regulatory documents on indicators "Microbiological purity." To ensure the microbiological stability of the preparations, it is necessary to eliminate the factors associated with microbial contamination, therefore we carried out experimental studies on the choice of preservative and its concentration for the developed gel. According to the results of experimental studies on the effectiveness of antimicrobial preservatives in gel samples, the following data were obtained. Samples of the studied gel with sodium preservatives benzoate 0.5 % and nipagin 0.2 % meet the criterion "A" according to the requirements of SPHU for drugs for skin application. But, according to research results, the antimicrobial efficacy of the gel with the preservative nipagin 0.2 % was slightly higher (lg reduction in the number of viable Staphylococcus aureus ATCC 6538 cells was 3.32 and 4.81; Pseudomonas aeruginosa ATCC 9027 - 3.28 and 4.66 ; Candida albicans ATCC 885-653 - 3.50 and 4.09; Aspergillus brasiliensis ATCC 16404 - 3.10 and 4.00 (2 and 7 days, respectively) and the spectrum of antimicrobial action is wider, which will contribute to the quality of the rotated gel also during storage. Therefore, for further research, we will use nipagin 0.2 % as a preservative. Conclusions: The expediency of using nipagin 0.2 % as a part of a combined gel for the treatment of acute and chronic joint inflammation has been theoretically proved and experimentally proved